The Effects of Entrepreneurial Competencies and Networks towards the Success of Firms from Quantitative and Qualitative Lens - Fadzline Tamyez, Puteri; Azizanad, Azlinna; Ishak, Nazaruddin; Ali, Juhary (International Journal of Engineering and Technology, 2026)
The construction industry has made significant contribution to both the economy as well as the national development. Various researches has mentioned on high rates of failures and bankruptcies in construction projects. Thus, it is difficult to ignore the sustainability of this industry and for them to anticipate growth.This paper will focus on the impact of the entrepreneurs in terms of their competencies and networks towards their success in Malaysian construction companies.This study adopts the mixed-methods sequential explanatory design. As a result, a strong relationship between two factors; personal competency and entrepreneurial success, with (β=.41). Interesting findings from qualitative method were the emerging themes,which are personal, strategic management, learning, opportunity, social network and inter-organization network. These findings have important implications for developing a competitive edge, by integrating two main variables, entrepreneurial competencies and entrepreneurial networks. These elements will give support to their business growth, particularly among the SMEs.
Keywords: Entrepreneurial Competencies; Entrepreneurial Networks; Construction Firms; Small Medium Enterprises